Pengaruh Beban Pajak Tangguhan, Komite Audit Dan Komisaris Independen Terhadap Penghindaran Pajak - Liviana Syafei; Mita Sicillia (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine how the influence of deferred tax burden, audit committee, and independent commissioner on tax avoidance in industrial sector companies listed on the Indonesia Stock Exchange in 2019 - 2023. The independent variables in this study are deferred tax burden, audit committee and independent commissioner. While the dependent variable in this study is tax avoidance. The population in this study were 63 industrial sector companies listed on the Indonesia Stock Exchange in 2019 - 2023. This type of research is quantitative with the sampling technique method used, namely purposive sampling and obtained 15 industrial sector companies with an observation period of 5 (five) years so that the total observation data is 75. This study uses panel data regression analysis tests and classical assumptions and data is processed using Microsoft Excel and Eviews 12. The results of this study indicate that deferred tax burden and audit committee have no effect on tax avoidance, while independent commissioners have an effect on tax avoidance. However, deferred tax burden, audit committee and independent commissioner simultaneously affect tax avoidance.